Prevalence and Factors Associated with Preterm Birth in Urban Areas: Case-Control Study - Rozhan Khezri; Shaker Salarilak; Sepideh Jahanian (Journal of Health Sciences and Surveillance System)
Background: Preterm birth (PTB) is a significant global health issue, with the majority of preterm births occurring in low and middle-income countries (LMICs), including Iran. This study aimed to determine the prevalence of PTB and its associated factors in urban areas of Iran.Methods: Over one year, this case-control study included 387 pregnant women (129 cases and 258 controls) in Sardashat, Iran. Data were extracted from medical records. Gestational age was estimated through ultrasound in the first trimester. Statistical analyses were performed using logistic regression.Results: The prevalence of PTB was 7.43%. Multivariable logistic regression analysis revealed a significant association between PTB and the following factors: education levels, antenatal care (ANC) visits [Adjusted Odds Ratio (AOR)=7.91 (95% CI: 2.43–25.71)], premature rupture of membranes (PROM) [AOR=5.25 (95% CI: 2.01–13.74)], gestational diabetes mellitus (GDM) [AOR=5.27 (95% CI: 1.49–18.58)], and preeclampsia [AOR=9.47 (95% CI: 3.02–29.73)].Conclusion: Identifying pregnant women at risk of preterm birth is crucial, and treatments are available to reduce the risk. Our research suggests that factors such as education level, ANC visits, PROM, GDM, and preeclampsia predispose pregnant women to preterm birth.